Pemanfaatan Media Sosial dalam Meningkatkan Daya Saing UMKM Keripik Singkong dan Lidah Manis di Desa Pematang Serai, Provinsi Sumatera Utara, Kabupaten Langkat, Kecamatan Tanjung Pura - Muhammad Azy Rahmanda Lubis; Fadhila Isfa; Nurkomaria Nurkomaria; Azhela Dwi Aryani; Ramadhan Nasution (Nusantara: Jurnal Pengabdian kepada Masyarakat, 2026)
This study examines the utilization of social media in improving the competitiveness of cassava chips and lidah manis SMEs in Pematang Serai Village, Tanjung Pura District, Langkat Regency, North Sumatra Province. The rapid development of information technology has encouraged SMEs to shift from conventional marketing methods to more effective and efficient digital marketing practices. This research employs a descriptive qualitative approach, with data collected through field observations, in-depth interviews, and documentation involving SME actors. The results indicate that the use of social media platforms such as WhatsApp, Facebook, and Instagram is able to expand market reach, increase product visibility, and strengthen relationships between business owners and consumers. Attractive promotional content, consistency in posting, and responsive communication are proven to influence consumer buying interest and trust. However, SMEs still face challenges, including limited digital literacy, time management constraints, and the lack of structured marketing strategies. Therefore, continuous training and assistance are needed so that SMEs can optimize the use of social media more effectively. This study is expected to serve as a reference for the development of digital-based SMEs in rural areas.